Pengaruh Electronic Word Of Mouth (E-Wom) terhadap Keputusan Pembelian Konsumen di Marula Coffee and Hungry Pasaman Barat - Gusrilia Nelsa; Adek Kurnia Fiza (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
This research aims to find problems related to electronic word of mouth on consumer purchasing decisions. This research uses quantitative descriptive research with a causal associative approach to determine the influence of electronic word of mouth on purchasing decisions. This research sampled 204 respondents from a population of 1,654 per month using purposive sampling techniques. Data was collected through a questionnaire distributed via Google Form with a Likert scale. The data collection technique was carried out using a questionnaire with a Likert scale that had been tested for validity and reliability. The collected data was analyzed using SPSS 20.00. The results of this research show that the electronic word of mouth variable is in the good category, namely with an average value of 3.74, and the purchasing decision variable shows the good category with an average value of 3.77. For the electronic word of mouth (X) value, the calculated F value is 910.753 with Sig 0.000 <0.05, meaning that the electronic word of mouth variable can explain the purchasing decision variable significantly. Furthermore, an Adjusted R Square value of 0.818 was obtained, meaning that the influence of the electronic word of mouth (X) variable on the purchasing decision variable (Y) was 81.8%, while 18.8% was influenced by other factors.